A plasmonic dipole optical antenna coupled quantum dot infrared photodetector. (22nd October 2015) - Mojaverian, Neda; Gu, Guiru; Lu, Xuejun
Abstract: In this paper, we report a full-wavelength plasmonic dipole optical antenna coupled quantum dot infrared photodetector (QDIP). The plasmonic dipole optical antenna can effectively modify the EM wave distribution and convert free-space propagation infrared light to localized surface plasmonic resonance (SPR) within the nanometer (nm) gap region of the full-wavelength dipole antenna. The plasmonic dipole optical antenna coupled QDIP shows incident-angle-dependent photocurrent enhancement. The angular dependence follows the far-field pattern of a full-wavelength dipole antenna. The directivity of the plasmonic dipole optical antenna is measured to be 1.8 dB, which agrees well with the antenna simulation. To our best knowledge, this is the first report of the antenna far-field and directivity measurement. The agreement of the detection pattern and the directivity with antenna theory confirms functions of an optical antenna are similar to that of a RF antenna.